If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = kx + f Reorder the terms: y = f + kx Solving y = f + kx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = f + kx
| 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W | | 3(9+1)-5=(2y-2) | | k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= | | 8y+20=16-12 | | 7/2x=-21 | | 6x-5=8x+13 | | e^2x=1/9 | | -54+12x=6(x-3) | | F=1/9k(d-n) | | 6-3/4x=9 | | 6a^2-10=422 |